The influence of plant saponins on the elasticity parameters of the great arteries in patients with multifocal atherosclerosis - Alfred R. Bogdanov (Concilium Medicum, 2021)
Background. Among the goals of pathogenetic therapy in patients with multifocal atherosclerosis, not only control of the intensity of atherogenesis, but also the elastic properties of the arterial system is becoming increasingly important, which opens up additional ways to reduce overall and cardiovascular mortality in this category of patients.